Visual Management Studies: Empirical and Theoretical Approaches. (14th June 2012) - Bell, Emma; Davison, Jane
Abstract : The field of visual research in management studies is developing rapidly and has reached a point of maturity where it is useful to bring together and evaluate existing work in this area and to critically assess its current impact and future prospects. Visual research is broadly defined to encompass a variety of forms, including pictures, graphs, film, web pages and architecture. It also incorporates work from several sub‐disciplines (organization studies, marketing, accounting, human resources, tourism and IT), and includes research based on pre‐existing visual material and studies that use researcher‐generated visual data. The authors begin by considering the growing recognition of the visual turn in management research as a counterweight to the linguistic turn, while also discussing reasons for resistance to visual approaches. Next, they review research that uses visual methods to study management and organization and suggest that visual management studies may be categorized according to whether methods used are empirically driven or theory based. This categorization highlights the philosophical, theoretical and interdisciplinary underpinnings of visual management studies. It also enables the visual to be accorded a status equivalent to linguistic meaning, through dispelling the realist assumptions that have impeded analytical development of visual management studies to date. Abstract : Video Abstract.